The challenges of divine determinism: a philosophical analysis - Furlong, Peter (Cambridge University Press, 2019)
A primer on divine determinism -- Divine determinism and free will: the consequence argument -- Divine determinism and free will: manipulation arguments -- Divine determinism and the author of sin objection -- Divine determinism and the blameworthiness objection -- Divine determinism and the free will defense -- God, determined agents, and love -- Divine commands, the divine will, and divine blame.